Lagos Soundscapes. Emeka Ogboh, 2019. Berlin, Germany: Kerber. 164 colour and 85 b/w illustrations, bibliography, index, list of works, 216 pp. - King, Kathleen W. (International Library of African Music, 2022)
pages: 134-137
Keywords: Lagos Soundscapes; African Music